THE IMPACT OF CONTRACT FARMING ON THE PROFIT OF VIRGINIA TOBACCO FARMING IN LOMBOK ISLAND, WEST NUSA TENGGARA - Hamidi, Hirwan (Journal of Indonesian Economy and Business, 2010)
This study aims at explaining the impact of contract farming on the profit of Virginia tobacco farming in Lombok Island. Does partnership influence profit? We used surveydata of 147 farmers, they are partners of tobacco processors and independent farmers. By utilizing profit function analysis, it is concluded that: (1) partnership positively affected the profit of Virginia tobacco farming in Lombok Island; (2) productivity, prices of tobacco, fertilizers (NPK, KNO), pesticide, kerosene, and labor wage significantly affected the profit. These are followed by: (1) that farmers should reduce the use of human labor, while partner company and local government should endeavor to find alternative technology to substitute human labor with machinery labor; (2) that the government is recommended to continue subsidy provisionof at least for short term program until cheaper alternative fuels, such as coal, solar energy, biomass energy, or others, are available.Keywords: impact, partnership, profit, Virginia tobacco